PEMBUATAN ALAT KEAMANAN BRANKAS MENGGUNAKAN KARTU AKSES BERBASIS MIKROKONTROLER ATMEGA16 - Santoso Setiawan; Selvi Novita Sari (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2013)
The more crimes like theft happen everywhere including at home. For that, it is necessary to provide security solutions to these precious objects and also provide comfort to the user. Designing a safe security system using an access card works with infrared sensors, giving the sign if the door is open safes LED indicator lights up, and the buzzer sounds. By means of a safe security system using security access card is expected to be a valuable object storage area can be increased.